1983
DOI: 10.1128/jcm.18.4.849-857.1983
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Candida albicans phenotypes from different geographical and anatomical sources

Abstract: Strain phenotypes of 330 Candida albicans isolates from five areas in the United States were determined on the basis of nine biochemical tests. Statistical analysis of the distribution of phenotypes revealed no significant differences among types from different anatomical sources. However, there were some differences among the phenotypes of strains from the different geographical areas, and there were substantial differences in biochemical phenotypes associated with strains susceptible and resistant to 5-fluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
13
0
4

Year Published

1985
1985
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(20 citation statements)
references
References 7 publications
3
13
0
4
Order By: Relevance
“…Data from the current and other studies imply that the phenotype A1R may be more widely distributed in Europe than in other regions of the world (Table 4). This tends to confirm the findings of Odds et al (13), who found geographical differences in C. albicans phenotypes from the United States and Great Britain. Interestingly, the phenotype A1R has been mainly associated with active infections and not with asymptomatic carriers, indicating its possible greater virulence in comparison to the other phenotypes (33).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Data from the current and other studies imply that the phenotype A1R may be more widely distributed in Europe than in other regions of the world (Table 4). This tends to confirm the findings of Odds et al (13), who found geographical differences in C. albicans phenotypes from the United States and Great Britain. Interestingly, the phenotype A1R has been mainly associated with active infections and not with asymptomatic carriers, indicating its possible greater virulence in comparison to the other phenotypes (33).…”
Section: Discussionsupporting
confidence: 91%
“…There are several articles describing phenotypes and genotypes of C. albicans derived from varying oral and geographical sites (6,7,13,15,25,(30)(31)(32)(33). However, such information on C. albicans isolates from root canal infections is scarce.…”
mentioning
confidence: 99%
“…Attempts to analyze candidal strain-related differenees in human disease have generally not been stieeessful (10,21,22), and this failure is undoubtedly due to the complex nature of both exogenous and endogenous factors affecting luiman caiididiasis. Thus, the clinical presentation of the disease eould be influenced by any one of the several factors, such as host immune status, diet, salivary flow rate and salivary composition, endocrine disturbances, use ot antibiotics or steroids, and presence ol dentures (23).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism behind the ability of this fungus to cause recurrent disease is unknown. It is postulated that one factor that may influence this is a decrease in susceptibility to antifungal agents (7,8), and this may be related to certain types of C. albicans (9). Because of this, many attempts have been made to search for particularly virulent types of C. albicans using a number of techniques, such as serotyping (10), biotyping (11), morphotyping (12,13) and genotyping (14,15).…”
mentioning
confidence: 99%